2010
DOI: 10.1177/0022466910369942
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Mathematics and Science Standards to Students With Moderate and Severe Developmental Disabilities

Abstract: This study evaluated strategies to teach secondary math and science content to students with moderate and severe developmental disabilities in a quasiexperimental group design with special education teachers randomly assigned to either the math or the science treatment group. Teachers in the math group implemented four math units representing four of the five national math standards. The science teachers implemented four science units representing three of eight national science content standards. A fourth sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 16 publications
1
95
0
5
Order By: Relevance
“…Twelve studies, meeting inclusionary criteria, were included in this literature review with a total of 426 participants with disabilities. Studies were grouped by the following disability categories: specific learning disabilities (Aydveniz Cihak, Graham, & Retinger, 2012;Bay, Staver, Bryan, & Hale, 1992;Dalton, Morocco, Tivnan, & Mead, 1997;Mastropieri, Scruggs, Norland, Berkeley, McDuffie, Tornquist, & Connors, 2006;McCarthy, 2005;McCleery & Tindal, 1999;& Scruggs et al, 1993); intellectual disabilities (Browder, Trela, Courtade, Jimenez, Knight, & Flowers, 2012;Courtade, Browder, Spooner, & DiBiase, 2010;Jimenez, Browder, Spooner, & DiBiase, 2012;McCarthy, 2005;& Smith, Spooner, Jimenez, & Browder, 2013); emotional/behavioral disabilities (Bay et al, 1992;Mastropieri et al, 2006;& McCarthy, 2005); autism spectrum disorder (Aydveniz et al, 2012); multiple disabilities (Smith et al, 2013); attention deficit hyperactivity disorder (McCarthy, 2005); and non-specified (Lynch, Taymans, Watson, Ochsendorf, Pyke, & Szesze, 2007) (See Table 2 for more detailed information).…”
Section: Participants Disability Types and Settingsmentioning
confidence: 99%
“…Twelve studies, meeting inclusionary criteria, were included in this literature review with a total of 426 participants with disabilities. Studies were grouped by the following disability categories: specific learning disabilities (Aydveniz Cihak, Graham, & Retinger, 2012;Bay, Staver, Bryan, & Hale, 1992;Dalton, Morocco, Tivnan, & Mead, 1997;Mastropieri, Scruggs, Norland, Berkeley, McDuffie, Tornquist, & Connors, 2006;McCarthy, 2005;McCleery & Tindal, 1999;& Scruggs et al, 1993); intellectual disabilities (Browder, Trela, Courtade, Jimenez, Knight, & Flowers, 2012;Courtade, Browder, Spooner, & DiBiase, 2010;Jimenez, Browder, Spooner, & DiBiase, 2012;McCarthy, 2005;& Smith, Spooner, Jimenez, & Browder, 2013); emotional/behavioral disabilities (Bay et al, 1992;Mastropieri et al, 2006;& McCarthy, 2005); autism spectrum disorder (Aydveniz et al, 2012); multiple disabilities (Smith et al, 2013); attention deficit hyperactivity disorder (McCarthy, 2005); and non-specified (Lynch, Taymans, Watson, Ochsendorf, Pyke, & Szesze, 2007) (See Table 2 for more detailed information).…”
Section: Participants Disability Types and Settingsmentioning
confidence: 99%
“…Researchers have found that students with severe disabilities, including those with ASD and ID, were able to participate in lessons aligned with biology, life science, and chemistry/ physical science standards with adaptations that included teacher-directed inquiry (e.g., experiments to discover a concept), explicit instruction in science vocabulary, handson materials , graphic organizers (Knight, Spooner, Browder, Smith, & Wood, 2013), and explicit e-text (Knight, Wood, Spooner, Browder, & O'Brien, in press). Researchers have found that students with severe disabilities, including those with ASD and ID, were able to participate in lessons aligned with biology, life science, and chemistry/ physical science standards with adaptations that included teacher-directed inquiry (e.g., experiments to discover a concept), explicit instruction in science vocabulary, handson materials , graphic organizers (Knight, Spooner, Browder, Smith, & Wood, 2013), and explicit e-text (Knight, Wood, Spooner, Browder, & O'Brien, in press).…”
Section: Considerations For Alternate Achievementmentioning
confidence: 99%
“…Maccini and Gagnon (2002) reported that many special education teachers had limited knowledge of national mathematics standards and focus instruction solely on basic mathematics. Limited instructional models that currently exist for teachers to teach mathematics to students with ASD focus on standards related to basic numbers and operations or money management (Browder et al 2012;Spencer et al 2014). Recent reviews of literature found limited research evidence on teaching mathematics to students with ASD (Knight et al 2013;Spencer et al 2014).…”
Section: Fractions Interventions For Students With Asdmentioning
confidence: 99%